The Short Stories of Ruskin Bond are the subject of this thematic investigation. - Bhargavi; Suresh, M. (The journal of contemporary issues in business and government, 2020)
Observing daily tiny happenings from the lovely hills of Mussoorie, two vigilant eyes have been transforming them into the inspiration for numerous great literary works from the comfort of their home. These are the eyes of a normal-looking guy who is constantly immersed in his fantasies, as shown here. Despite his unfocused demeanour, he was a source of amusement for the group of people.vChildren and adults alike will benefit from this programme. A large number of people go up to the Mussoorie hills merely to have a glimpse of him. For a big number of his readers, he has almost become a celebrity in their eyes. Despite the fact that he has a name and is well-known, He has gained notoriety and recognition in the field of Indian-English writing, yet he prefers the life of a private individual. a person who is completely committed to nature Key words: exploration, alienation, loneliness, homelessness, running away from home, and human. Family and parental failure, separation, and the termination of a relationship are all topics that come up in conversations about relationships. both a source of discomfort and pleasure